Identification of an Acinetobacter baumannii zinc acquisition system that facilitates resistance to calprotectin-mediated zinc sequestration. - M Indriati Hood; Brittany L Mortensen; Jessica L Moore; Yaofang Zhang; Thomas E Kehl-Fie; Norie Sugitani; Walter J Chazin; Richard M Caprioli; Eric P Skaar (PLoS Pathogens)
Acinetobacter baumannii is an important nosocomial pathogen that accounts for up to 20 percent of infections in intensive care units worldwide. Furthermore, A. baumannii strains have emerged that are resistant to all available antimicrobials. These facts highlight the dire need for new therapeutic strategies to combat this growing public health threat. Given the critical role for transition metals at the pathogen-host interface, interrogating the role for these metals in A. baumannii physiology and pathogenesis could elucidate novel therapeutic strategies. Toward this end, the role for calprotectin- (CP)-mediated chelation of manganese (Mn) and zinc (Zn) in defense against A. baumannii was investigated. These experiments revealed that CP inhibits A. baumannii growth in vitro through chelation of Mn and Zn. Consistent with these in vitro data, Imaging Mass Spectrometry revealed that CP accompanies neutrophil recruitment to the lung and accumulates at foci of infection in a murine model of A. baumannii pneumonia. CP contributes to host survival and control of bacterial replication in the lung and limits dissemination to secondary sites. Using CP as a probe identified an A. baumannii Zn acquisition system that contributes to Zn uptake, enabling this organism to resist CP-mediated metal chelation, which enhances pathogenesis. Moreover, evidence is provided that Zn uptake across the outer membrane is an energy-dependent process in A. baumannii. Finally, it is shown that Zn limitation reverses carbapenem resistance in multidrug resistant A. baumannii underscoring the clinical relevance of these findings. Taken together, these data establish Zn acquisition systems as viable therapeutic targets to combat multidrug resistant A. baumannii infections.